PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT MEMBACA DAN MENULIS AYAT AL-QUR’AN Studi kasus di SMP Ungglan Al-Ittihad Rejoslamet Mojowano - Farera, Putri Ayu; Surur, Shobihus (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2022)
Abstract : This scientific research aims to describe and analyze the role of a teacher in the process of learning to read and write at the Al-Ittihat Rejoslamet Mojowarno Superior Junior High School. A descriptive approach was taken in this study. Observations, interviews, and documentation are examples of data collection methods. The primary data sources were obtained from 3 students of Al-Ittihat Rejoslamet Mojowarno Superior Middle School, 1 PAI teacher, and the Principal of Al-Ittihat Superior Middle School. Meanwhile, secondary data sources include books, document files, and researcher notes; researcher documentation and other supports; and statistics on the number of students and professors at Al-Ittihat Rejoslamet Mojowarno Superior Junior High School.In this study, it was found that PAI teachers played an important role in fostering interest in reading and writing verses of the Qur'an, as evidenced by three reading indicators: (1) fluency in reading the Qur'an, (2) accuracy in reading the Qur'an in tajwid, and (3) the suitability of the reading with its makhraj. In addition, there are three types of writing indicators: writing single letters, writing vowels, and writing conjunctions containing many letters, sentences, and phrases.